Utilização do metabolismo protéico ( 15N-glicina) na detecção precoce de agravamento da atividade da doença em pacientes portadores de retocolite ulcerativa inespecífica - Dichi, Isaias; Dichi, Jane B.; Frenhane, Patrícia [UNESP]; Corrêa, Camila Renata [UNESP]; Angeleli, Aparecida Y.O. [UNESP]; Bicudo, Mitsue H. [UNESP]; Rodrigues, Maria A.M. [UNESP]; Victória, Carlos R. [UNESP]; Burini, Roberto Carlos [UNESP] (My University, 1998)
Disease activity was assessed in 10 (five males and five females) ulcerative colitis patients through the following parameters: clinical, laboratory, sigmoidoscopic and histological. Protein metabolism was also assessed with 15N-glycine and urinary ammonia as end product. Only one patient had exacerbation of the disease two months after the study started. This patient presented in the beginning of the study protein synthesis and breakdown of 4.51 and 3.47 g protein/kg/day, respectively, values higher than all other patients, showing an hypermetabolic state, suggesting an increase of the disease activity. However, this increase was not detected by others indicators and indexes utilised. These data allow to suggest the hypothesis that protein metabolism predicts precociously the exacerbation of disease activity in ulcerative colitis patients.
Precocious detection of disease exacerbation in ulcerative colitis patients using kinetic study with 15N-glycine
Keywords: Colitis, ulcerative; Proteins, biosynthesis; Proteins, metabolism; glycine; protein; female; hospitalization; human; male; metabolism; middle aged; ulcerative colitis; Colitis, Ulcerative; Female; Glycine; Humans; Male; Middle Aged; Proteins; Severity of Illness Index